2006
DOI: 10.1093/annonc/mdj034
|View full text |Cite
|
Sign up to set email alerts
|

Long-term cardiac toxicity after adjuvant epirubicin-based chemotherapy in early breast cancer: French Adjuvant Study Group Results

Abstract: After a long-term follow-up, epirubicin-related LVD risk was acceptable (1.36%) with one toxic death (0.04%). In 78% of cases, LVD were transient or well controlled.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
41
3
4

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 100 publications
(50 citation statements)
references
References 20 publications
2
41
3
4
Order By: Relevance
“…The number of cardiac events was identical and the incidence of decrease in LVEF during the follow-up period was 0.8 and 2.1%, respectively, without any development of subsequent cardiac complications or CHF. These results confirmed observations reported from our whole FASG database, which showed that the use of epirubicin-based adjuvant chemotherapy was associated with a low risk of left ventricular dysfunctions ( [Fumoleau et al, 2006). When epirubicin was delivered within recommended doses, a favourable benefit/risk ratio was maintained.…”
Section: Discussionsupporting
confidence: 89%
“…The number of cardiac events was identical and the incidence of decrease in LVEF during the follow-up period was 0.8 and 2.1%, respectively, without any development of subsequent cardiac complications or CHF. These results confirmed observations reported from our whole FASG database, which showed that the use of epirubicin-based adjuvant chemotherapy was associated with a low risk of left ventricular dysfunctions ( [Fumoleau et al, 2006). When epirubicin was delivered within recommended doses, a favourable benefit/risk ratio was maintained.…”
Section: Discussionsupporting
confidence: 89%
“…8 Anthracycline cardiotoxicity comprises both an early toxicity, generally light and reversible, and a late toxicity, dose-dependent and irreversible. 9 Cardiotoxicity severity is also variable and ranges from abnormalities that become apparent only during exercise 2 to severe congestive heart failure (CHF). 4 Swain et al 10 estimated the incidence of Doxorubicin-induced CHF at 5.1%.…”
Section: Discussionmentioning
confidence: 99%
“…2 This process is particularly true for reporting side effects associated with administration of systemic chemotherapy. [3][4][5][6][7][8][9][10][11][12][13][14][15] However, clinical trials generally have rigid eligibility criteria, often excluding elderly patients, pregnant women, patients with multiple coexisting diseases, and those taking medications suspected of interacting with the study drug. 16,17 Therefore, study participants (motivated volunteers) in clinical trials often represent a much more homogeneous patient population in terms of gender, age, race/ethnicity, and comorbidity, and they are not representative of the population at large, particularly the elderly population who are often substantially underrepresented in clinical trials.…”
mentioning
confidence: 99%
“…31,32 Several reports have been published on chemotherapy-associated cardiac complications, particularly anthracycline-containing agents that are known to be associated with a range of cardiotoxic syndromes. [11][12][13] Cardiotoxicity may occur either immediately at the time of drug administration or months to years after treatment. Two studies recently examined the incidence of congestive heart failure associated with chemotherapy for breast cancer and found a 14% to 35% increase in risks for those receiving chemotherapy.…”
mentioning
confidence: 99%